Performance Diagnostic Checklist – human services: adaptação e aplicação em uma empresa brasileira - Rocha, Glauce Gomes da (2016)
Some methods may be used to identify variables that maintain or limit classes of behaviors. The performance diagnostic tool called Performance Diagnostic Checklist - Human Services (PDC-HS), can be a useful tool in identifying functional variables, as well as indicating possible interventions to be implemented when there are performance problems. This research aimed to (1) Translate and adapt this tool that focuses on the verbal report of the leadership and the direct observations of the applicator, (2) create a team version to be answered by the employees, and (3) their respective applications in a business services company. The method consisted of seven steps, as follows: 1º) first check: students of the fifth year of Psychology, 2º) second check: Application in a pilot class of the company's management, 3º) third check: Appraisers experts in behavior analysis, 4º) fourth check: management team and direction of the company researched, 5º) defining and redefining the performance problem, 6º) fifth check: PDC-HS application of the target group and 7º) analysis. The results of the application of the tools in the different audiences are complementary. After the applications of PDC-HS in the researched company, 14 interventions were indicated in which seven are compatible actions between leadership and employees and seven are actions that would be appropriate based on the verbal report of the employees and that were not indicated on the basis of leadership’s verbal report. For future studies there is the need for customization of the tool, depending on the behavioral description of the performance problem, target audience and institution